Prove the following trigonometric identities.
Answers
Answered by
2
Answer with Step-by-step explanation:
Given : sinθ/(1− cosθ) = cosecθ + cotθ
L.H.S = sinθ/(1− cosθ)
= [sinθ (1 + cosθ)] / [(1− cosθ) (1 + cosθ)]
[By rationalising ]
= sinθ(1+ cosθ)/(1− cos²θ)
[By using the identity, (a- b)(a + b) = a² – b²]
= [sinθ + (sinθ × cosθ)] /sin²θ
[By using the identity, (1- cos²θ) = sin²θ]
= ( sinθ /sin²θ ) + (sinθ × cosθ/sin²θ)
= 1/sinθ + cosθ/sinθ
= cosec θ + cot θ
[By using the identity, cosec θ =1/sinθ & cosθ/sinθ = cot θ]
sinθ/(1− cosθ) = cosecθ + cotθ
L.H.S = R.H.S
Hence Proved..
HOPE THIS ANSWER WILL HELP YOU...
Answered by
0
Refer to the attatchment..
Thanks
Attachments:
![](https://hi-static.z-dn.net/files/d07/f340587910b59721ffc7d901e63660b5.jpg)
Similar questions